FEASIBILITY STUDY OF ROAD SUB BASE COURSE USING SIRTU KONAWEHA BASED ON CBR VALUES - Al Tafakur La Ode (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
Pavement is one part of the traffic lane that functions to provide services to land transportation facilities. For good road construction foundation media, quality cannot be separated from quality. The Konaweha area contains Sirtu which is quite abundant and has the potential to be used as a road pavement construction material. One way to test the quality of sirtu is by testing it in the laboratory using the California Bearing Ratio (CBR) tool. Sirtu is an extension of rock sand, which is the most widely needed C mineral. the tests were carried out at the Satria Jaya Sentosa Laboratory, namely testing for water content, sieving, specific gravity, abrasion, Atterberg limits, clay lumps, proctor and CBR. The results of the CBR and proctor test characteristics of Sirtu Konaweha Village were based on research conducted in the laboratory, namely Specific gravity = 2.754 gram/cc, Optimum MC = 5.25%, ?d Max. 100 % = 2.222 gram/cm3, ?d Max. 95% = 2.111 gram/cm3, planned CBR Value 1” (Inc) = 68%. From the test results it meets the requirements of the 2010 Bina Marga specification as a subbase layer material.